If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -6) + -1(2x + -8) = 1 Reorder the terms: (-6 + x) + -1(2x + -8) = 1 Remove parenthesis around (-6 + x) -6 + x + -1(2x + -8) = 1 Reorder the terms: -6 + x + -1(-8 + 2x) = 1 -6 + x + (-8 * -1 + 2x * -1) = 1 -6 + x + (8 + -2x) = 1 Reorder the terms: -6 + 8 + x + -2x = 1 Combine like terms: -6 + 8 = 2 2 + x + -2x = 1 Combine like terms: x + -2x = -1x 2 + -1x = 1 Solving 2 + -1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 1 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 1 + -2 -1x = 1 + -2 Combine like terms: 1 + -2 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| P=3+7t | | 10x+4=-3x-17+5x-4 | | x-2(3)=8 | | 5=-3x-3y | | x-8y=-1 | | 3.2=8.73+x | | 10y-5=27y-90 | | 8x-3(2x+3)=-3 | | x-9y=-2 | | -10=5(w-4) | | 5+7=7+5 | | 10v=-16v+182 | | 12(x+5)=16(x+3) | | 9(l+2)=3(l-3) | | 2x+3(10-x)=25 | | 8+2x=7x-2 | | 15x+73=-347 | | 2(4x-5)-3(-x+6)=2/5(15x-65) | | 8x-12+4=8x-8 | | -5+7x=-4x+39 | | 3x+15+5x=-1 | | 3d^2+7d-6=0 | | 2y=3y-15 | | -3n(4b)+2a(3b)= | | 10x-9=2x-69 | | 8(2x+1)=4x-6x | | 12-6x=5-3+15x | | -5x-5=-5x | | 3(2x-5)=-39 | | 14+2x=-9-5x+4x | | 7g=49 | | y=-1/4+1 |